2022
DOI: 10.25139/ijair.v4i2.5267
|View full text |Cite
|
Sign up to set email alerts
|

Semi-supervised Learning Models for Sentiment Analysis on Marketplace Dataset

Abstract: Sentiment analysis aims to categorize opinions using an annotated corpus to train the model. However, building a high-quality, fully annotated corpus takes a lot of effort, time, and expense. The semi-supervised learning technique efficiently adds training data automatically from unlabeled data. The labeling process, which requires human expertise and requires time, can be helped by an SSL approach. This study aims to develop an SSL-Model for sentiment analysis and to compare the learning capabilities of Naive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Moreover, the sentiments of people towards Moroccan universities were assessed using RF, MNB, LR DT, SVM, and XGboost, as well as the results indicated that the highest accuracy at 98% [20]. Another sentiment analysis was also conducted on a marketplace dataset using naï ve Bayes and random forest and the highest accuracy was achieved by Naï ve Bayes at 87% [21]. Nine algorithms were also analyzed using five datasets and the most accurate result of 85.1% was recorded in Naï ve Bayes, RF, and LR [22].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the sentiments of people towards Moroccan universities were assessed using RF, MNB, LR DT, SVM, and XGboost, as well as the results indicated that the highest accuracy at 98% [20]. Another sentiment analysis was also conducted on a marketplace dataset using naï ve Bayes and random forest and the highest accuracy was achieved by Naï ve Bayes at 87% [21]. Nine algorithms were also analyzed using five datasets and the most accurate result of 85.1% was recorded in Naï ve Bayes, RF, and LR [22].…”
Section: Introductionmentioning
confidence: 99%